(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Everything around us is online, virtual, automated, adapted individually to each person. The development of information technology has contributed to the uprising of a new marketing branch so-called "one on one" marketing. Beacon technology with its simplicity of implementation and wide application capabilities, provides great benefits in retailing, shopping malls, museums, airports, hospitals and sport complexes, which are experimenting with beacons technology and are using them for various purposes depending on the context. This paper presents the importance of the application of information technologies in the business the Post of Serbia in order to modernize and automate IT as a strategic advantage over the competition.It is suggested to use beacon technology in Serbian Post as a desirable technology for enhancing and personalizing the user experience. By applying this will be bridged the gap between traditional and digital payments, which is well established in the postal sector. The aim of the paper is to point out the importance of monitoring new technologies and analyzing the possibilities of their application in different activities.